Ruptured Primary Ovarian Pregnancy: A Rare Case Report - Shrestha, Abha; Chawla, CD; Shrestha, RM (Kathmandu University Medical Journal, 2013)
Ovarian pregnancy is an uncommon presentation of ectopic gestation and usually, it ends with rupture before the end of the first trimester. Its presentation often is difficult to distinguish from that of tubal ectopic pregnancy and hemorrhagic ovarian cyst. We report a rare primary ruptured ovarian pregnancy in a 26 years lady. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 76-77 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8026